Où est "ailleurs" ? Sémantique lexicale de l'adverbe spatial "ailleurs". - Marie Lammert (Corela, 2013)
Like other words, we think that the French spatial adverbial ailleurs contains two kinds of information: a conceptual meaning and a procedural meaning that depends on the semantico-referential process it involves. This article postulates that ailleurs is an anaphoric adverbial (within a memorial conception of anaphora) and not a deictical one (position defended in Stein-Zintz, 2008). In this case, anaphora resolution requires a spatial reference point and ailleurs’s reference is established in contrast and in opposition with it. The reader will also find the outline of a typology of ailleurs’s uses and some remarks about the fact that ailleurs is not applied to the conceptual domain of time.